Treating eating disorders in the real world - MaiStep: a skill-based universal prevention for schools - Bürger, Arne; Kaess, Michael (Preventive medicine, 2019)
Eating disorders are difficult to treat and often associated with morbidity and mortality. Universal prevention approaches are increasingly focusing on enhancing skills, but few eating disorder programs are available for under-15-year-olds. This study aimed to develop and examine a school-based universal prevention program (‘MaiStep’) for adolescent boys and girls. A three-arm randomized controlled trial with baseline, post-intervention and 12-month follow-up was conducted with 1654 adolescents (M=13.35, SD 0.76). ‘MaiStep’ was delivered by psychologists in the first intervention group (IG1) and teachers in the second intervention group (IG2), and compared to an active control group (ACG). Primary outcomes were eating disorder-related risk factors measured with scales of the Eating Disorder Inventory-2 (e.g. ‘drive for thinness’, ‘interoceptive awareness’), cognitions and affect related to the body (Body Shape Questionnaire, BSQ-8), and behaviors (Body Image Avoidance Questionnaire, BIAQ). The total sample (N1) was divided into a healthy subsample (N2) and a sample fulfilling DSM-5 criteria for a subthreshold eating disorder (N3) measured with the self-report Structured Inventory for Anorexic and Bulimic Syndromes (SIAB-S). Significant improvements in ‘interoceptive awareness’ (EDI-2) and lower BIAQ scores emerged in N1 at post-intervention and at 12-month follow-up (F(4; 3038)=3.068, p=.016, ηpart2=0.004 and F(4; 2900)=2.993, p=.018, ηpart2=0.004) and in N2 at post-intervention and at 12-month follow-up (F(4; 2812)=3.147, p=.014, ηpart2=0.004 and F(4; 2684)=3.674, p=.005, ηpart2=0.005). The healthy subsample N2 additionally showed significantly lower scores on ‘drive for thinness’ (EDI-2) and on the BSQ-8c at post-intervention (F(2; 1446)=3.091, p=.046, ηpart2=0.004 and F(2; 1453)=3.505, p=.030, ηpart2=0.005) but not at 12-month follow-up. No significant results emerged for N3. The positive findings of improved ‘interoceptive awareness’ (EDI-2) and reduced body image avoidance (BIAQ) indicate that broad disseminated universal prevention under the age of 15 is possible. Trial registration MaiStep is registered at the German Clinical Trials Register (DRKS00005050).